Eiríksjökull plateau icefield landsystem, Iceland. - Evans, D.J.A.; Ewertowski, M.; Orton, C. (Journal of Maps, 2016)
A 1:9500 scale map of the Eiríksjökull plateau icefield and its post-Little Ice Age (LIA) foreland geomorphology and surficial geology is presented as a modern exemplar of an asymmetrically developed mountain glacier typical of the style of glacierization that dominated during mid-latitude Quaternary cold stages. Features regarded as diagnostic for this setting include (a) ice-cored hummocky terrain, indicative of controlled moraine construction in polythermal snouts, and localized breach lobe development, incremental stagnation and rock glacierization, all indicative of a debris-charged glacier snout; (b) fluted till and moraines, indicative of temperate basal ice conditions up-ice from polythermal glacier margins and (c) glacifluvial and debris flow deposits, occurring as steep fans emanating from glacier snouts at the plateau edge and in ice-contact fans or ramps fed directly by debris-covered glacier margins at the LIA. Although this plateau icefield landsystem is similar to those previously reported from Iceland, a remarkable debris-covered snout/ice-cored moraine complex on the foreland of Klofajökull is a more extreme example of the depositional zone that characterizes the valleys surrounding the more sediment-starved plateau ice dispersal centres.